Milton, Spenser and The chronicles of Narnia : literary sources for the C.S. Lewis novels - Hardy, Elizabeth Baird, 1971- (Jefferson, N.C. : McFarland & Co., 2007)
"The Chronicles of Narnia were influenced by Spenser's The Faerie Queen and Milton's Paradise Lost. Lewis became renowned for studies of both authors. Examines Lewis's echo of each book, and how each conveys similar meanings. Chapters focus on the depiction of evil, female characters, fantastic and symbolic landscapes and settings, and the spiritual concepts important to Lewis"--Provided by publisher.
Includes bibliographical references (p. 163-181) and index.
Keywords: Lewis, C. S. -- 1898-1963; Spenser, Edmund, -- 1552?-1599 -- Influence; Spenser, Edmund, -- 1552?-1599.; Milton, John, -- 1608-1674 -- Influence; Milton, John, -- 1608-1674.; Lewis, C. S. -- 1898-1963; Christian literature, English -- History and criticism; Evil in literature; Spirituality in literature; Christianity in literature